The Contribution of Moralist Leadership to the Performance of State Primary School Teachers in Lubuk Basung District - Irawati; Yahya; Rifma; Anisah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The phenomenon found shows that the performance of state elementary school teachers in Lubuk Basung District is relatively low. This research aims to reveal whether the two factors of moralist leadership and adhocracy organizational culture contribute to the performance of state elementary school teachers in Lubuk Basung District. The hypothesis proposed in this research is: Moralist leadership contributes to teacher performance. The research population was 300 public elementary school teachers in Palembayan District. Sampling was carried out using a stratified proportional random sampling technique. The selected sample was 90 people. To test the hypothesis, correlation and regression analysis techniques are used. Data collection uses a questionnaire that has been tested for validity and reliability. The results of data analysis show that: Moralist leadership contributes 22.1% to teacher performance. The results of this research indicate that moralist leadership needs to be implemented by school principals to improve the performance of state elementary school teachers in Lubuk Basung District